The Development of Comics Based on Algebraic Literacy for 7th Grade Students of Junior High School - Azizah, Farida Nur; Cholily, Yus Mochamad; Cahyono, Hendarto (MEJ (Mathematics Education Journal), 2019)
This research aimed at describing the development process and the effectiveness of mathematics media using comics based on algebraic literacy for 7th-grade students of junior high school (SMP). The kind of research, that conducted, was Research and Development (R&D) by using the ADDIE model. In which the model was Analysis, Design, Development, Implementation, and Evaluation. The media was tested into 24 students of 7th-grade. The average result of the media validation test both the validators were 3,7 in which is categorized as very valid with a feasible description to be tested. While the average result of material validation was 3,39 which is categorized as very valid with a feasible description to be tested. The effectiveness analysis result obtained that the students gave very positive responses with the obtained percentages of 85,21% and the mastery percentages of the class were 87,5% ineffective category. Therefore, it can be concluded that the comics based on algebraic literacy is effective to be used in algebra material for 7th-grade students SMP.